Pengaruh Pengetahuan, Persepsi, dan Religiusitas terhadap Minat Menabung di Bank Syariah dengan Sikap sebagai Variabel Mediasi - Ahmad Ulul Mahasin; Khusnudin (FKDP (Forum Komunikasi Dosen Peneliti), 2026)
This study aims to analyze the influence of perception, religiosity, and knowledge on students’ saving interest in Islamic banks with attitude toward Islamic banking as a mediating variable. The study employed a quantitative approach using primary data collected through questionnaires distributed to university students in Malang City. Data analysis was conducted using Structural Equation Modeling-Partial Least Square (SEM-PLS). The results show that perception and knowledge significantly influence attitudes toward Islamic banking, but do not directly affect saving interest. Religiosity does not significantly influence either attitude or saving interest. Meanwhile, attitude toward Islamic banking has a highly significant effect on saving interest and becomes the most dominant variable in the research model. In addition, attitude is proven to fully mediate the influence of perception and knowledge on saving interest, but is unable to mediate the effect of religiosity. Overall, the findings indicate that students’ saving interest is more strongly influenced by affective factors in the form of attitudes formed through cognitive factors such as perception and knowledge. This study contributes to the development of Islamic financial behavior literature and provides implications for strengthening Islamic financial inclusion among students.